Determination of HLA Tissue Type According to the Etiology of Patients with Chronic Renal Failure - Burcu KARAKUS TURAN; Fahri UCAR; Vural Taner YILMAZ; Yahya KILINC; Sule DARBAŞ ARAS; Huseyin KOCAK; Nurten SAYIN EKINCI; Bulent AYDINLI; Habibe Sema ARSLAN (Medeniyet Medical Journal)
Objective: Chronic kidney disease (CKD) is a prominent public health concern, is defined as functional and structural damage to the kidneys. This study aims to investigate the association between human leukocyte antigen (HLA) alleles individuals with CKD and the different etiological subgroups of diesease. Methods: Genomic DNA was obtained from peripheral blood samples of 1,079 patients with retrospective CKD and 1,111 healthy control individuals. HLA genotyping was conducted using the Luminex based low-resolution method. Allele frequency distributions were calculated with the help of Arlequin v3.11 population genetics statistics program and SPSS v23.0 program, and p<0.05 values were accepted as significant by chi-square tests. Results: HLA A*02 (21.83%), B*35 (18.30%), DRB1*11 (21.41%) alleles were observed most frequently in individuals with CKD, respectively. In our study, B*08, B*49, B*50 alleles in the HLA B locus (p=0.002, p=0.012 p=0.009) and DRB1*03, *04 alleles in the HLA DRB1 locus (p<0.001, p<0.001) were found positively associated with CKD. A*02, A*11, A*74 alleles at the HLA A locus (p=0.003, p<0.001, p=0.009) and B*27, B*39, B* alleles at the HLA B locus 40, B*59 (p<0.001, p<0.001, p<0.001, p=0.009), DRB1*07, *08, *09, *13, *16 (p<0.001, p=0.012, p=0.007, p<0.001, p<0.001) alleles were determined as negatively associated with the disease. Among the etiological groups of CKD, cystic kidney disease (36.8%), hypertension (16.8%) and urological anomalies (16.6%) were negatively associated with the HLA-DR*13 allele. Conclusions: Since CKD shows serious morbidity and mortality, this comprehensive study of HLA subgroups gave an explanatory idea about which alleles associated with the disease in terms of susceptibility and protection.